Legal Voids in the Regulation of Immaterial Compensation and the Role of General Court Judges in Building Progressive Judicial Standards - Ismu Bahaiduri Febri Kurnia; Azis Budianto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the legal vacuum and normative ambiguity in the regulation of immaterial damages in Indonesian civil law and reconstruct the role of general court judges in developing progressive judicial standards. Normatively, Articles 1243, 1246, and 1365 of the Civil Code recognize the existence of